Pengembangan Aplikasi Manajemen Kelayakan Panen Budidaya Ikan Lele berbasis Website (Studi Kasus : Budidaya Lele Bapak Andri) - Yudha Prasetya Anza; Indriati Indriati; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The raising of catfish is urgently needed in agriculture. But there are still many growing countries that still manage by hand by logging on the development books. Of course, such measures are less effective because the likelihood of errors taking considerable time to record. In the proliferation of catfish, there is also a process of harvesting for the purpose of making it easier for the farmers to determine the worthiness of the crop by the established fish criteria. Therefore, the author create a web-based application to tax the feasibility of the catfish breeding crop to help the farmers carry out the feasibility process of harvesting. In the production of this application the author observes and interviews first to the development of the project, followed by the process of analysis of needs, design and implementation and testing. After analysis of needs, functional needs are provided by 28 (twenty-eight). The initiated design phase of architecture design, data design, component design, interface design and implemented using PHP programming language, HTML, JavaScript. The testing phase be done with the whitebox approach and the blackbox approach. Test results show that all functions that have been tested are valuable.